STRATEGIC DIRECTIONS FOR INNOVATIVE DEVELOPMENT OF ENTERPRISE FINANCIAL-ECONOMIC SECURITY SYSTEMS BASED ON DIGITAL TECHNOLOGIES - Олександр Правдивець; Наталія Літвін; Олег Денисов; Олександр Поліщук; Віталій Олійник (Фінансово-кредитна діяльність: проблеми теорії та практики)
A strategic approach has always been characterized by instability due to constant changes in the dynamics of the external environment in which modern enterprises operate. The intensification of directions for innovative development changes over time and depends on the current conditions of the enterprise's functioning. Digital technologies have transformed the situation, but the problem is whether they remain relevant over a prolonged period. Thus, the article aims to identify the current strategic directions for the innovative development of enterprise financial-economic security systems based on digital technologies. However, to highlight what is currently relevant, it is necessary to evaluate changes in their intensification over recent years to determine whether what worked several years ago can still yield proper results today. This will constitute the main scientific task. The research object is the financial-economic security of such open socio-economic systems as enterprises. The article identifies key strategic directions for the innovative development of enterprise financial-economic security systems in the IT sector, which are highly active in applying digital technologies. Comparing them through a method of comparisons by advantages, we determined the intensification over a specific period of more than five years, as this pertains to a strategic approach. IT and security experts were involved, and their opinions were processed through the Delphi method. As a result, despite minor fluctuations, the intensification of the strategic directions we identified has not changed significantly; therefore, they remain relevant today for enterprises in the IT sector. Given the existing restrictions in conditions of martial law, the practical application of the identified strategic directions was not realized. The restrictions also affected the industry specificity, as only the IT sector was considered. The further trajectory of research is to enable secure innovative development in the current conditions for IT sector enterprises.